PENDAMPINGAN UMKM BAKSO PANGSIT GEROBAK IJO SEBAGAI UPAYA UNTUK MENINGKATKAN PENDAPATAN USAHA - Eka Wijayanti; Meilinda Dwi Cahyaningsih; Wahyu Aulia Nur Zahara; Rikah; Damayanti (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
Micro, Small and Medium Enterprises or better known as MSMEs are a type of business owned by small entrepreneurs. MSMEs are a type of business that has assets and turnover that are still relatively small. However, one of the MSMEs, namely in the food and beverage sector, is able to grow up to 6% in 2024. One of the small and medium businesses in the culinary sector that has the potential to be developed is the MSME "Bakso pangsit gerobak ijo" owned by Mr So. This MSME is located in Leteh Village RT 03 / RW 01, Rembang District, Rembang Regency, Central Java. The MSME "Bakso pangsit gerobak ijo" is an MSME that produces Meatballs and Pangsit. In the observation and pre-implementation activities carried out by the KKU team, several obstacles were found that MSMEs faced in running their businesses, namely lack of marketing, business premises that were only in one location, lack of appearance improvements, not yet having business legality, no product identity, limited equipment, and poor financial management. Based on these problems, the KKU team created a mentoring program to help develop the MSMEs which was carried out at the implementation stage, namely by creating a Google Maps account and directions as a sign of the existence of MSMEs, providing education related to promotions, creating product logo designs, providing education on updating product displays, creating business legality, providing assistance with production equipment and providing education related to financial management and financial management for businesses. Through this program, it is hoped that the MSMEs "Bakso pangsit gerobak ijo" will be able to compete, increase sales and increase business income.